An experimental approach to assess the combined effects of multiple stressors on a large vertebrate species - Enrico Pirotta; Catriona M. Harris; Lori H. Schwacke; Len Thomas; Jason B. Allen; Aaron A. Barleycorn; Marco Casoli; Jonathan Crossman; Laura Aichinger Dias; Laura Engleby; Erin LaBrecque; Jenny A. Litz; et al. (Conservation Biology, 2026)
The design of experiments to investigate the combined effects of multiple stressors requires exposing target organisms to multiple combinations of stressor doses. Concurrent manipulation of stressors is often infeasible with wildlife, but long‐lasting health effects allow individual health to be used as an integrator of prior stressor exposure. The population of bottlenose dolphins in Barataria Bay, Louisiana, experienced long‐lasting health effects after exposure to oil from the Deepwater Horizon spill. We investigated whether compromised health status affects dolphins’ ability to respond to other stressors, specifically vessel traffic, potentially leading to increased collision risk. We used this case study to develop a hypothesis‐driven experimental approach to assess the combined effects of multiple stressors in a large, long‐lived vertebrate species. We conducted controlled vessel approaches to test whether the health status of targeted dolphins affected their behavioral responses. Our results highlighted some effects of health, suggesting that oil spills may exacerbate the effects of other stressors in coastal populations. For example, lung disease was associated with a delayed dive response, which could affect the ability to vertically avoid vessels and lead to increased collision risk. However, health effects on response probability were overall smaller than anticipated, and other contextual variables (e.g., sex, age, calf presence, prior experience, and exposure context) contributed to response variability. Our work demonstrated the value of formalizing stressor interactions as multidimensional dose–response functions and showed the feasibility of an experimental, multiple‐stressor study in a wild system in which individual health status can be used as an integrator of prior stressor exposure. This approach has broad implications for other species that are difficult to handle experimentally. The quantification and management of the cumulative risk from multiple stressors on wildlife will require a combination of empirical and mechanistic approaches to inform long‐term, population consequences.

Mammography screening in Tennessee: a tract-level spatial analysis of geographic and socioeconomic disparities - Sima Namin; Jonathan S. Wall; R. Eric Heidel; Ashton Brooks; Savannah Allen; Jennifer Ferris (Cancer Causes & Control, 2026)
Purpose Despite improvements in early detection, Tennessee ranks among the top ten states for breast cancer mortality among women. Mammography screening and early diagnosis are critical to reducing mortality, yet access and uptake vary widely across the State. We tested whether access to diagnostic services affected screening in the State. Methods We merged CDC PLACES estimates of screening among women aged 50–74 with geocoded FDA-certified mammography facilities to derive drive-time categories. Tract covariates included education, poverty, insurance, race/ethnicity, primary care provider density, urban/rural status, and Appalachian designation. We mapped hot/cold spots using Getis-Ord Gi* and fit four nested beta-regression models: geography only, socioeconomic only, combined, and combined plus log-provider density. Results Median screening prevalence was 74.8%. Hotspots clustered around Memphis, Nashville, and Knoxville; cold spots in Central Appalachian and western floodplain tracts. Geography explained ~ 23% of between-tract variation (pseudo- R 2 = 0.238); socioeconomic covariates ~ 61% (0.607). In combined models, drive-time and Appalachian effects attenuated. Urban tracts screened 0.72 percentage points (pp) higher than rural, and each 1-pp rise in adults without a high-school diploma predicted − 0.13 pp. Conclusion Urbanicity and education were the primary drivers of mammography screening disparities in Tennessee. To improve early diagnosis and outcomes, interventions should prioritize educational outreach, poverty reduction, insurance expansion, and improved geographic access, via mobile units or telehealth, targeting remote cold-spot tracts.

Microplastic Munchies: Exploring Microplastic Trophic Transfer Potential Between Two Key Prey Fish Species and Resident Common Bottlenose Dolphins ( Tursiops truncatus ) in Sarasota Bay, Florida - Estella Martin; Randall S. Wells; Elizabeth J. Berens McCabe; Miranda K. Dziobak; Savannah M. Case; Tita Curtin; Eric Conger; Ayushi Gaur; Millie A. Knowles; Robyn Faulkner Allen; Christina N. Toms; John E. Weinstein; et al. (Marine Mammal Science, 2026)
Microplastics have been identified in hundreds of species, with evidence of trophic transfer via contaminated prey. Sarasota Bay common bottlenose dolphins ( Tursiops truncatus ) serve as sentinels of coastal pollution, including plastics and chemical plasticizers. Previous research confirmed microplastic ingestion in these dolphins (100.0%, n = 7) and extensive contamination in 11 common prey species (96.5%, n = 86). This study compared microplastic characteristics in dolphins, Gulf toadfish ( Opsanus beta , n = 30) and pinfish ( Lagodon rhomboides , n = 35), to assess potential trophic transfer. Dolphin ingestion was evaluated using gastric ( n = 23) and fecal ( n = 15) samples from catch‐and‐release health assessments (2022–2024), while prey gastrointestinal and muscle tissues were screened. Particles were prevalent across samples (dolphins: 82.6%, pinfish: 97.1%, toadfish: 96.7%), with fibers as the dominant shape. Raman spectroscopy confirmed plastic polymers (PL, PP, and PET) in all species. Pinfish had a higher median particle load (1.4 particles/g tissue) than toadfish (0.6 particles/g tissue; p = 0.006). Based on estimated daily food intake (5.96–6.45 kg) and diet composition (toadfish—34.1%, pinfish—38.1%), Sarasota dolphins may ingest more than 10,000 particles/day from these fish alone. Contaminated prey may be vectors for dolphin microplastic exposure. This study emphasizes the need for further research on microplastic pathways in marine food webs and implications for wildlife.

Implications for modeling anion exchange treatment of perfluoroalkyl substances in drinking water and related natural organic impacts: a pilot study - Samantha J. Smith; David G. Wahman; Eric J. Kleiner; Brooke N. Gray; Toby T. Sanan; Eva K. Stebel; Cameron X. Gastaldo; Esther W. Hughes; Sophia G. Pedigo; Boris Datsov; Malcolm F. Lathrop-Allen; Isabella L. Bass; et al. (Water Research, 2026)

Policy implications of net-zero emissions: A multi-model analysis of United States emissions and energy system impacts - John E.T. Bistline; Matthew Binsted; Geoffrey Blanford; Gale Boyd; Morgan Browning; Yongxia Cai; Jae Edmonds; Allen A. Fawcett; Jay Fuhrman; Ruying Gao; Chioke Harris; Christopher Hoehne; et al. (Energy and Climate Change, 2025)

Comparing phthalate exposure between bottlenose dolphins (Tursiops truncatus) residing in urban and rural environments - Miranda K. Dziobak; Tita Curtin; Randall S. Wells; Ryan Takeshita; Cynthia R. Smith; Eric Zolman; Christina N. Toms; Robyn F. Allen; Leslie B. Hart (Frontiers in Marine Science, 2025)
Introduction Exposure to phthalate esters has previously been documented in bottlenose dolphins ( Tursiops truncatus ) inhabiting an urban estuary (Sarasota Bay, FL, USA; 2010-2019). Phthalates are chemicals commonly added to plastic products and consumer goods to enhance qualities such as flexibility, fragrance, and stability. Chemical leaching from products into the marine environment leaves wildlife vulnerable to reproductive, developmental, and metabolic impairment. Environmental phthalate exposure has been shown to vary relative to human activity and urbanization. Methods To evaluate potential differences in dolphin exposure risk, urine was collected from free-ranging bottlenose dolphins residing in an urban (Sarasota Bay, FL, USA; 2010-2024; n=71) and rural estuary (Barataria Bay, LA, USA; 2011- 2023; n=45). Urinary phthalate metabolite concentrations were quantified with high-performance liquid chromatography (HPLC; Agilent 1100; WatersXBridge BEH C18, 2.5 μm, 2.1x50 mm analytical column) coupled to a triple quadrupole mass spectrometer (MS; Applied Biosystems Sciex API 4000) with an electrospray ionization (ESI negative) interface. Results The magnitude of MEHP detection did not differ significantly between sampling sites (p=0.97); however, MEHP was detected more frequently in Sarasota Bay dolphins (73.24%; n=52; 95% CI: 61.20-82.73) than Barataria Bay dolphins (33.33%; n=15; 95% CI: 20.00-48.95%). Dolphins from Sarasota Bay may be exposed to a greater diversity of phthalates compared to Barataria Bay dolphins, indicated by differences in the detected phthalate metabolite profile. Discussion Notably, dolphins from Barataria Bay were impacted by the Deepwater Horizon oil spill, with evidence suggesting long-term negative health outcomes. The endocrine-disrupting effects of phthalates could exacerbate metabolic, reproductive, or immune dysfunction in dolphins, especially those with compromised health. The higher phthalate detection frequency in Sarasota Bay dolphins suggests increased urban exposure risks; however, detection in dolphins from Barataria Bay raises concerns for dolphins in recovering ecosystems. Further research is needed to assess potential synergistic impacts of chemical mixtures, and targeted mitigation strategies in contaminated environments.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Sustaining Productivity while Reducing Methane Emission in Calcareous Soils: Implications of Combining Inorganic Fertilizer and Biochar - Agbesi Kwadzo Keteku; Isaac Kodzo Amegbor; Stephen Yeboah; Patricia Amankwaa-Yeboah; Richard Dormatey; Kennedy Agyeman; Mavis Badu Brempong; Ernest Baafi; Maxwell Darko Asante; Allen Oppong; Samuel Aduse Poku; Eric Owusu Danquah; et al. (International Journal of Plant Production, 2025)
A considerable proportion of applied nutrients are adsorbed by the calcite surface of calcareous soils, making them unavailable to plants. A combination of organic amendments and fertilizers can improve nutrient retention and mineralization, and also reduce greenhouse gas (GHG) emissions. A two-years field experiment was undertaken to investigate the impacts of inorganic fertilizer, biochar and silicon on nutrient uptake, growth, yield and post-harvest soil chemistry in calcareous soil using rice ( Oryza sativa L.) as a test crop. The implication of each treatment on methane emissions was also investigated. The combination of NPK, biochar and silicon significantly improved rice growth, yield, P and Si uptake; and post-harvest soil nutrition. Biochar increased soil organic carbon content between 4.2 and 108.5% across the years. An increase from 2.4 to 6.1% was observed in the inorganic fertilizer treatments, 11.4–12.0% for the biochar treatments and 2.5–19.0% for ½NPK + biochar from 2020 to 2021. Maximum grain yield was achieved with the treatment ½NPK + biochar + 100 kg Si ha − 1 which was comparable to NPK + 100 kg Si ha − 1 . Also, the combination of ½NPK + biochar + 50 kg Si reduced CH 4 emissions and produced a comparable yield to NPK + 50 kg Si in both years. While further research is required to explore the effects of the length of time biochar is applied on reducing CH 4 emissions, this study suggests a basis for predicting the impact of biochar on the management of CH 4 emissions in calcareous soils.

Exposed and Vulnerable: Sources and Health Implications of Chemical Exposures in Neonatal, Pediatric, and Cardiac Intensive Care Units - Jordan R. Kuiper; Melania Bembea; J. William Gaynor; David Graham; Eric M. Graham; Kurunthachalam Kannan; Nikki G. Posnack; Allen D. Everett; Jessie P. Buckley (Current Environmental Health Reports, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

An expert‐based system to predict population survival rate from health data - Lori H. Schwacke; Len Thomas; Randall S. Wells; Teresa K. Rowles; Gregory D. Bossart; Forrest Townsend; Marilyn Mazzoil; Jason B. Allen; Brian C. Balmer; Aaron A. Barleycorn; Ashley Barratclough; Louise Burt; et al. (Conservation Biology, 2024)
Timely detection and understanding of causes for population decline are essential for effective wildlife management and conservation. Assessing trends in population size has been the standard approach, but we propose that monitoring population health could prove more effective. We collated data from 7 bottlenose dolphin ( Tursiops trun catus) populations in the southeastern United States to develop a method for estimating survival probability based on a suite of health measures identified by experts as indices for inflammatory, metabolic, pulmonary, and neuroendocrine systems. We used logistic regression to implement the veterinary expert system for outcome prediction (VESOP) within a Bayesian analysis framework. We fitted parameters with records from 5 of the sites that had a robust network of responders to marine mammal strandings and frequent photographic identification surveys that documented definitive survival outcomes. We also conducted capture–mark–recapture (CMR) analyses of photographic identification data to obtain separate estimates of population survival rates for comparison with VESOP survival estimates. The VESOP analyses showed that multiple measures of health, particularly markers of inflammation, were predictive of 1‐ and 2‐year individual survival. The highest mortality risk 1 year following health assessment related to low alkaline phosphatase (odds ratio [OR] = 10.2 [95% CI: 3.41–26.8]), whereas 2‐year mortality was most influenced by elevated globulin (OR = 9.60 [95% CI: 3.88–22.4]); both are markers of inflammation. The VESOP model predicted population‐level survival rates that correlated with estimated survival rates from CMR analyses for the same populations (1‐year Pearson's r = 0.99, p = 1.52 × 10 –5 ; 2‐year r = 0.94, p = 0.001). Although our proposed approach will not detect acute mortality threats that are largely independent of animal health, such as harmful algal blooms, it can be used to detect chronic health conditions that increase mortality risk. Random sampling of the population is important and advancement in remote sampling methods could facilitate more random selection of subjects, obtainment of larger sample sizes, and extension of the approach to other wildlife species.

Geography, taxonomy, extinction risk and exposure of fully migratory birds to droughts and cyclones - Rhys G. G. Preston‐Allen; Henry Häkkinen; Laura Cañellas‐Dols; Eric I. Ameca y Juarez; C. David L. Orme; Nathalie Pettorelli (Global Ecology and Biogeography, 2024)
Aim Anthropogenic climate change is predicted to drive unprecedented increases in the frequency and intensity of extreme climatic events, such as drought and cyclones. The impacts of these events on fully migratory species could be particularly severe and have cascading effects on the functioning of many ecosystems. We explore the relationships between geography, taxonomy, extinction risk and the exposure of fully migratory birds to drought and cyclones. Location Global. Time Period 1985–2014. Major Taxa Studied 383 fully migratory bird species. Methods We assessed the exposure of fully migratory birds to cyclones and droughts, quantifying exposure by calculating the percentage of spatial overlap between a species' range and the extent of an extreme event within a given time series. We compared the level of cumulative exposure sustained by species among different taxonomic groups and within their breeding and wintering ranges; we also assessed whether species currently classed as ‘threatened’ are more cumulatively exposed than ‘non‐threatened’ species. Results We identified fully migratory bird species highly exposed to extreme climatic events and global geographic hotspots of species exposure. 4% of species were found to be highly exposed to cyclones and droughts in both their wintering and breeding ranges. Wintering ranges were, on average, more cumulatively exposed to cyclones than breeding ranges; there was no discernible difference in drought exposure between ranges. Species currently classed as threatened were shown to experience higher exposure to droughts than non‐threatened ones in both ranges. Main Conclusions This exposure analysis provides the first step to a full global assessment of fully migratory bird species' vulnerability to extreme climatic events. Many species are at least as exposed to extreme events within their wintering ranges as in their breeding ranges, supporting calls for ‘full cycle’ assessment of migratory species' vulnerability to climate change. Our identification of hotspots of exposure may help to guide further monitoring, research and management.

Observations of the chemistry and concentrations of reactive Hg at locations with different ambient air chemistry - Mae Sexauer Gustin; Sarrah M. Dunham-Cheatham; Natalie Allen; Nicole Choma; William Johnson; Sam Lopez; Armistead Russell; Eric Mei; Olivier Magand; Aurélien Dommergue; Tyler Elgiar (Science of The Total Environment, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Late Cenozoic history and the role of Beringia in assembling a Holarctic cestode species complex - Kurt E. Galbreath; Arseny A. Makarikov; Kayce C. Bell; Stephen E. Greiman; Julie M. Allen; Genevieve M.S. Haas; Chenhong Li; Joseph A. Cook; Eric P. Hoberg (Molecular Phylogenetics and Evolution, 2023)

Development and Evaluation of High-Density SNP Arrays for the Eastern Oyster Crassostrea virginica - Ximing Guo; Jonathan B. Puritz; Zhenwei Wang; Dina Proestou; Standish Allen; Jessica Small; Klara Verbyla; Honggang Zhao; Jaime Haggard; Noah Chriss; Dan Zeng; Kathryn Lundgren; et al. (Marine Biotechnology, 2023)

Understanding heterogeneity of responses to, and optimizing clinical efficacy of, exercise training in older adults: NIH NIA Workshop summary - Melissa L. Erickson; Jacob M. Allen; Daniel P. Beavers; Linda M. Collins; Karina W. Davidson; Kirk I. Erickson; Karyn A. Esser; Matthijs K. C. Hesselink; Kerrie L. Moreau; Eric B. Laber; Charlotte A. Peterson; Courtney M. Peterson; et al. (GeroScience, 2023)
Exercise is a cornerstone of preventive medicine and a promising strategy to intervene on the biology of aging. Variation in the response to exercise is a widely accepted concept that dates back to the 1980s with classic genetic studies identifying sequence variations as modifiers of the VO 2 max response to training. Since that time, the literature of exercise response variance has been populated with retrospective analyses of existing datasets that are limited by a lack of statistical power from technical error of the measurements and small sample sizes, as well as diffuse outcomes, very few of which have included older adults. Prospective studies that are appropriately designed to interrogate exercise response variation in key outcomes identified a priori and inclusive of individuals over the age of 70 are long overdue. Understanding the underlying intrinsic (e.g., genetics and epigenetics) and extrinsic (e.g., medication use, diet, chronic disease) factors that determine robust versus poor responses to various exercise factors will be used to improve exercise prescription to target the pillars of aging and optimize the clinical efficacy of exercise training in older adults. This review summarizes the proceedings of the NIA-sponsored workshop entitled, “Understanding Heterogeneity of Responses to, and Optimizing Clinical Efficacy of, Exercise Training in Older Adults” and highlights the importance and current state of exercise response variation research, particularly in older adults, prevailing challenges, and future directions.

Do host‐associated microbes show a contrarian latitudinal diversity gradient? Insights from Mytilus californianus , an intertidal foundation host - Alexander T. Neu; Eric E. Allen; Kaustuv Roy (Journal of Biogeography, 2021)
Aim The latitudinal diversity gradient (LDG) is one of the most pervasive large‐scale trends in biodiversity. However, whether microbial taxa also conform to this pattern remains poorly known. This study uses the gill and shell‐surface microbiomes of the marine bivalve Mytilus californianus to test whether the diversity of host‐associated microbial communities declines with increasing latitude, as predicted by the LDG. Location Northeastern Pacific coast, ranging from Sitka, AK to La Jolla, CA, USA (spanning 24.12 degrees of latitude). Taxon Bacteria and Archaea associated with M. californianus gills and shell‐surfaces. Methods We amplified and sequenced the 16S rRNA gene from M. californianus gill and shell‐surface samples. We used linear and quadratic regressions, accounting for spatial autocorrelation when needed, of average alpha and gamma diversities of the whole microbiome, as well as individual microbial clades, to determine whether these taxa conformed to the traditional LDG. We also used permutational multivariate analysis of variance to determine the level of compositional differentiation among sampling sites. Results Gill and shell‐surface microbiota show differing latitudinal diversity patterns, with both micro‐environments exhibiting high levels of compositional differentiation along latitude. Individual microbial clades within each micro‐environment also show different latitudinal trends, most likely due to differing ecologies and life histories. Main conclusions Mytilus californianus ‐associated microbial taxa show a flat, hump‐shaped or contrarian LDG, suggesting that a steep decline in diversity with increasing latitude may not be a universal pattern across different domains of life.

High Throughput Argon-37 Field System - James C. Hayes; Craig Aalseth; Thomas Alexander; Henning Back; Eric Church; Michael Foxe; Todd Hossbach; Paul Humble; Lance Lidey; Emily Mace; Kerry Meinhardt; Jennifer Mendez; et al. (Pure and Applied Geophysics, 2021)

Neuropsychological Assessment and Screening in Heart Failure: a Meta-Analysis and Systematic Review - Eric J. Connors; Alexander O. Hauson; Brianna D. Barlet; Sharis Sarkissians; Nicholas P. Stelmach; Alyssa D. Walker; Natasha M. Nemanim; Kristina L. Greenwood; Nicholas J. Chesher; Scott C. Wollman; Kenneth E. Allen; Matthew G. Hall; et al. (Neuropsychology Review, 2021)

Impacts of the Marine Hatchery Built Environment, Water and Feed on Mucosal Microbiome Colonization Across Ontogeny in Yellowtail Kingfish, Seriola lalandi - Jeremiah J. Minich; Barbara Nowak; Abigail Elizur; Rob Knight; Stewart Fielder; Eric E. Allen (Frontiers in Marine Science, 2021)
The fish gut microbiome is impacted by a number of biological and environmental factors including fish feed formulations. Unlike mammals, vertical microbiome transmission is largely absent in fish and thus little is known about how the gut microbiome is initially colonized during hatchery rearing nor the stability throughout growout stages. Here we investigate how various microbial-rich surfaces from the built environment “BE” and feed influence the development of the mucosal microbiome (gill, skin, and digesta) of an economically important marine fish, yellowtail kingfish, Seriola lalandi , over time. For the first experiment, we sampled gill and skin microbiomes from 36 fish reared in three tank conditions, and demonstrate that the gill is more influenced by the surrounding environment than the skin. In a second experiment, fish mucous (gill, skin, and digesta), the BE (tank side, water, inlet pipe, airstones, and air diffusers) and feed were sampled from indoor reared fish at three ages (43, 137, and 430 dph; n = 12 per age). At 430 dph, 20 additional fish were sampled from an outdoor ocean net pen. A total of 304 samples were processed for 16S rRNA gene sequencing. Gill and skin alpha diversity increased while gut diversity decreased with age. Diversity was much lower in fish from the ocean net pen compared to indoor fish. The gill and skin are most influenced by the BE early in development, with aeration equipment having more impact in later ages, while the gut “allochthonous” microbiome becomes increasingly differentiated from the environment over time. Feed had a relatively low impact on driving microbial communities. Our findings suggest that S. lalandi mucosal microbiomes are differentially influenced by the BE with a high turnover and rapid succession occurring in the gill and skin while the gut microbiome is more stable. We demonstrate how individual components of a hatchery system, especially aeration equipment, may contribute directly to microbiome development in a marine fish. In addition, results demonstrate how early life (larval) exposure to biofouling in the rearing environment may influence fish microbiome development which is important for animal health and aquaculture production.

Decade‐scale stability and change in a marine bivalve microbiome - Alexander T. Neu; Ian V. Hughes; Eric E. Allen; Kaustuv Roy (Molecular Ecology, 2021)
Predicting how populations and communities of organisms will respond to anthropogenic change is of paramount concern in ecology today. For communities of microorganisms, however, these predictions remain challenging, primarily due to data limitations. Information about long‐term dynamics of host‐associated microbial communities, in particular, is lacking. In this study, we use well‐preserved and freshly collected samples of soft tissue from a marine bivalve host, Donax gouldii , at a single site to quantify the diversity and composition of its microbiome over a decadal timescale. Site‐level measurements of temperature, salinity and chlorophyll a allowed us to test how the microbiome of this species responded to two natural experiments: a seasonal increase in temperature and a phytoplankton bloom. Our results show that ethanol‐preserved tissue can provide high‐resolution information about temporal trends in compositions of host‐associated microbial communities. Specifically, we found that the richness of amplicon sequence variants (ASVs) associated with D . gouldii did not change significantly over time despite increases in water temperature (+1.6°C due to seasonal change) and chlorophyll a concentration (more than ninefold). The phylogenetic composition of the communities, on the other hand, varied significantly between all collection years, with only six ASVs persisting over our sampling period. Overall, these results suggest that the diversity of microbial taxa associated with D . gouldii has remained stable over time and in response to seasonal environmental change over the course of more than a decade, but such stability is underlain by substantial turnover in the composition of the microbiome.

Sierra Nevada mountain lake microbial communities are structured by temperature, resources and geographic location - Marika A. Schulhof; Andrew E. Allen; Eric E. Allen; Natalie Mladenov; John P. McCrow; Natalie T. Jones; Jessica Blanton; Hamanda B. Cavalheri; Drishti Kaul; Celia C. Symons; Jonathan B. Shurin (Molecular Ecology, 2020)
Warming, eutrophication (nutrient fertilization) and brownification (increased loading of allochthonous organic matter) are three global trends impacting lake ecosystems. However, the independent and synergistic effects of resource addition and warming on autotrophic and heterotrophic microorganisms are largely unknown. In this study, we investigate the independent and interactive effects of temperature, dissolved organic carbon (DOC, both allochthonous and autochthonous) and nitrogen (N) supply, in addition to the effect of spatial variables, on the composition, richness, and evenness of prokaryotic and eukaryotic microbial communities in lakes across elevation and N deposition gradients in the Sierra Nevada mountains of California, USA. We found that both prokaryotic and eukaryotic communities are structured by temperature, terrestrial (allochthonous) DOC and latitude. Prokaryotic communities are also influenced by total and aquatic (autochthonous) DOC, while eukaryotic communities are also structured by nitrate. Additionally, increasing N availability was associated with reduced richness of prokaryotic communities, and both lower richness and evenness of eukaryotes. We did not detect any synergistic or antagonistic effects as there were no interactions among temperature and resource variables. Together, our results suggest that (a) organic and inorganic resources, temperature, and geographic location (based on latitude and longitude) independently influence lake microbial communities; and (b) increasing N supply due to atmospheric N deposition may reduce richness of both prokaryotic and eukaryotic microbes, probably by reducing niche dimensionality. Our study provides insight into abiotic processes structuring microbial communities across environmental gradients and their potential roles in material and energy fluxes within and between ecosystems.

Site Fidelity of Oyster Reef Blennies and Gobies in Saltmarsh Tidal Creeks - Juliana M. Harding; Dennis M. Allen; Eric R. Haffey; Kyle M. Hoffman (Estuaries and Coasts, 2020)

Monocyte activation, HIV, and cognitive performance in East Africa - L. Arnoldo Muñoz-Nevárez; Brandon M. Imp; Michael A. Eller; Francis Kiweewa; Jonah Maswai; Christina Polyak; Omalla Allan Olwenyi; I. Elaine Allen; Eric Rono; Benedetta Milanini; Hannah Kibuuka; Julie A. Ake; et al. (Journal of NeuroVirology, 2020)

Association between vitamin content, plant morphology and geographical origin in a worldwide collection of the orphan crop Gynandropsis gynandra (Cleomaceae) - E. O. Dêêdi Sogbohossou; Dieke Kortekaas; Enoch G. Achigan-Dako; Patrick Maundu; Tsvetelina Stoilova; Allen Van Deynze; Ric C. H. de Vos; M. Eric Schranz (Planta, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

The Journey to AAPS 2020: a Reflection from Strategic Planning to PharmSci 360 - Joseph W. Polli; Christopher R. McCurdy; Dale Eric Wurster; Binodh S. DeSilva; Annette Bak; Reina Bendayan; Bernd Meibohm; Allen C. Templeton; William Weiser (The AAPS Journal, 2019)

Andromonoecy in Gynandropsis gynandra (L.) Briq. (Cleomaceae) and effects on fruit and seed production - Herbaud P. F. Zohoungbogbo; Carlos A. Houdegbe; Dêêdi E. O. Sogbohossou; Monique G. Tossou; Patrick Maundu; Eric M. Schranz; Allen Van Deynze; Jeanne Zoundjihekpon; Enoch G. Achigan-Dako (Genetic Resources and Crop Evolution, 2018)

The Journey to AAPS 2020: a Reflection from Strategic Planning to PharmSci 360 - Joseph W. Polli; Christopher R. McCurdy; Dale Eric Wurster; Binodh S. DeSilva; Annette Bak; Reina Bendayan; Bernd Meibohm; Allen C. Templeton; William Weiser (AAPS PharmSciTech, 2018)

Metabolic potential and in situ transcriptomic profiles of previously uncharacterized key microbial groups involved in coupled carbon, nitrogen and sulfur cycling in anoxic marine zones - Alvaro M. Plominsky; Nicole Trefault; Sheila Podell; Jessica M. Blanton; Rodrigo De la Iglesia; Eric E. Allen; Peter von Dassow; Osvaldo Ulloa (Environmental Microbiology, 2018)
Summary Anoxic marine zones (AMZs) impact biogeochemical cycles at the global scale, particularly the nitrogen cycle. Key microbial players from AMZs have been identified, but the majority remains unrecognized or uncharacterized. Thirty‐one single‐cell amplified genomes (SAGs) from the eastern tropical North and South Pacific AMZs were sequenced to gain insight into the distribution, metabolic potential and contribution to the community transcriptional profile of these uncharacterized bacterial and archaeal groups. Detailed analyses focused on SAG‐bins assigned to three of these groups that presented 79%–100% estimated genome completeness: the putative sulphur‐oxidizing Gamaproteobacteria EOSA II clade, a Marinimicrobia member of the recently recognized PN262000N21 clade found to be abundant in AMZ anoxic cores, and a representative of the Marine Benthic Group A Thaumarchaeota. Community‐based analyses revealed that these three groups are significantly more abundant and transcriptionally more active in the AMZ microbial communities than previously described phylogenetically related microbial groups. Collectively, these groups have the potential to link biogeochemically relevant processes by coupling the carbon, nitrogen and sulfur cycles. Together, these results increase our understanding of key microbial components inhabiting AMZs and other oxygen‐deficient marine environments, enhancing our capacity to predict the impact of the expansion of these ecosystems due to climate change.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The effects of climate change associated abiotic stresses on maize phytochemical defenses - Martha M. Vaughan; Anna Block; Shawn A. Christensen; Leon Hartwell Allen; Eric A. Schmelz (Phytochemistry Reviews, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

Phytosanitary measures to reduce the movement of forest pests with the international trade of wood products - Eric Allen; Meghan Noseworthy; Michael Ormsby (Biological Invasions, 2017)

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

The oral microbiota in patients with pancreatic cancer, patients with IPMNs, and controls: a pilot study - Sara H. Olson; Jaya Satagopan; Youming Xu; Lilan Ling; Siok Leong; Irene Orlow; Amethyst Saldia; Peter Li; Pamela Nunes; Vincent Madonia; Peter J. Allen; Eileen O’Reilly; et al. (Cancer Causes & Control, 2017)

Topsoil Thickness Influences Nitrogen Management of Switchgrass - Matt A. Yost; Newell R. Kitchen; Kenneth A. Sudduth; Allen L. Thompson; Eric Allphin (BioEnergy Research, 2017)

High pCO2 and elevated temperature reduce survival and alter development in early life stages of the tropical sea hare Stylocheilus striatus - Eric J. Armstrong; Trevor R. Allen; Maeva Beltrand; Vaimiti Dubousquet; Jonathon H. Stillman; Suzanne C. Mills (Marine Biology, 2017)

First-in-human studies of seletalisib, an orally bioavailable small-molecule PI3Kδ inhibitor for the treatment of immune and inflammatory diseases - Eric Helmer; Mark Watling; Emma Jones; Dominique Tytgat; Mark Jones; Rodger Allen; Andrew Payne; Annelize Koch; Eugene Healy (European Journal of Clinical Pharmacology, 2017)

Effort rights‐based management - Dale Squires; Mark Maunder; Robin Allen; Peder Andersen; Kepa Astorkiza; Douglas Butterworth; Gonzalo Caballero; Raymond Clarke; Hans Ellefsen; Patrice Guillotreau; John Hampton; Rögnvaldur Hannesson; et al. (Fish and Fisheries, 2017)
Effort rights‐based fisheries management ( RBM ) is less widely used than catch rights, whether for groups or individuals. Because RBM on catch or effort necessarily requires a total allowable catch ( TAC ) or total allowable effort ( TAE ), RBM is discussed in conjunction with issues in assessing fish populations and providing TAC s or TAE s. Both approaches have advantages and disadvantages, and there are trade‐offs between the two approaches. In a narrow economic sense, catch rights are superior because of the type of incentives created, but once the costs of research to improve stock assessments and the associated risks of determining the TAC and costs of monitoring, control, surveillance and enforcement are taken into consideration, the choice between catch or effort RBM becomes more complex and less clear. The results will be case specific. Hybrid systems based on both catch and effort are increasingly employed to manage marine fisheries to capture the advantages of both approaches. In hybrid systems, catch or effort RBM dominates and controls on the other supplements. RBM using either catch or effort by itself addresses only the target species stock externality and not the remaining externalities associated with by‐catch and the ecosystem.

Long-term T-DNA insert stability and transgene expression consistency in field propagated sugarcane - Kerry Hosmer Caffall; Chengkun He; Michele Smith-Jones; Kristin Mayo; Pearl Mai; Shujie Dong; John Ke; Erik Dunder; Michele Yarnall; Rachel Whinna; Joe DeMaio; Weining Gu; et al. (Plant Molecular Biology, 2017)

Neural Cell Adhesion Molecule NrCAM Is Expressed in the Mammalian Inner Ear and Modulates Spiral Ganglion Neurite Outgrowth in an In Vitro Alternate Choice Assay - Yves Brand; Michael Sung; Kwang Pak; Eduardo Chavez; Eric Wei; Vesna Radojevic; Daniel Bodmer; Allen F. Ryan (Journal of Molecular Neuroscience, 2015)

An agenda for assessing and improving conservation impacts of sustainability standards in tropical agriculture - Jeffrey C. Milder; Margaret Arbuthnot; Allen Blackman; Sharon E. Brooks; Daniele Giovannucci; Lee Gross; Elizabeth T. Kennedy; Kristin Komives; Eric F. Lambin; Audrey Lee; Daniel Meyer; Peter Newton; et al. (Conservation Biology, 2015)
Sustainability standards and certification serve to differentiate and provide market recognition to goods produced in accordance with social and environmental good practices, typically including practices to protect biodiversity. Such standards have seen rapid growth, including in tropical agricultural commodities such as cocoa, coffee, palm oil, soybeans, and tea. Given the role of sustainability standards in influencing land use in hotspots of biodiversity, deforestation, and agricultural intensification, much could be gained from efforts to evaluate and increase the conservation payoff of these schemes. To this end, we devised a systematic approach for monitoring and evaluating the conservation impacts of agricultural sustainability standards and for using the resulting evidence to improve the effectiveness of such standards over time. The approach is oriented around a set of hypotheses and corresponding research questions about how sustainability standards are predicted to deliver conservation benefits. These questions are addressed through data from multiple sources, including basic common information from certification audits; field monitoring of environmental outcomes at a sample of certified sites; and rigorous impact assessment research based on experimental or quasi‐experimental methods. Integration of these sources can generate time‐series data that are comparable across sites and regions and provide detailed portraits of the effects of sustainability standards. To implement this approach, we propose new collaborations between the conservation research community and the sustainability standards community to develop common indicators and monitoring protocols, foster data sharing and synthesis, and link research and practice more effectively. As the role of sustainability standards in tropical land‐use governance continues to evolve, robust evidence on the factors contributing to effectiveness can help to ensure that such standards are designed and implemented to maximize benefits for biodiversity conservation.

Host genetics and viral load in primary HIV-1 infection: clear evidence for gene by sex interactions - Xuelin Li; Matthew A. Price; Dongning He; Anatoli Kamali; Etienne Karita; Shabir Lakhi; Eduard J. Sanders; Omu Anzala; Pauli N. Amornkul; Susan Allen; Eric Hunter; Richard A. Kaslow; et al. (Human Genetics, 2014)

Biomass changes and trophic amplification of plankton in a warmer ocean - Guillem Chust; J. Icarus Allen; Laurent Bopp; Corinna Schrum; Jason Holt; Kostas Tsiaras; Marco Zavatarelli; Marina Chifflet; Heather Cannaby; Isabelle Dadou; Ute Daewel; Sarah L. Wakelin; et al. (Global Change Biology, 2014)
Ocean warming can modify the ecophysiology and distribution of marine organisms, and relationships between species, with nonlinear interactions between ecosystem components potentially resulting in trophic amplification. Trophic amplification (or attenuation) describe the propagation of a hydroclimatic signal up the food web, causing magnification (or depression) of biomass values along one or more trophic pathways. We have employed 3‐D coupled physical‐biogeochemical models to explore ecosystem responses to climate change with a focus on trophic amplification. The response of phytoplankton and zooplankton to global climate‐change projections, carried out with the IPSL Earth System Model by the end of the century, is analysed at global and regional basis, including European seas ( NE A tlantic, B arents S ea, B altic S ea, B lack S ea, B ay of B iscay, A driatic S ea, A egean S ea) and the Eastern Boundary Upwelling System (Benguela). Results indicate that globally and in A tlantic M argin and N orth S ea, increased ocean stratification causes primary production and zooplankton biomass to decrease in response to a warming climate, whilst in the B arents, B altic and B lack S eas, primary production and zooplankton biomass increase. Projected warming characterized by an increase in sea surface temperature of 2.29 ± 0.05 °C leads to a reduction in zooplankton and phytoplankton biomasses of 11% and 6%, respectively. This suggests negative amplification of climate driven modifications of trophic level biomass through bottom‐up control, leading to a reduced capacity of oceans to regulate climate through the biological carbon pump. Simulations suggest negative amplification is the dominant response across 47% of the ocean surface and prevails in the tropical oceans; whilst positive trophic amplification prevails in the A rctic and A ntarctic oceans. Trophic attenuation is projected in temperate seas. Uncertainties in ocean plankton projections, associated to the use of single global and regional models, imply the need for caution when extending these considerations into higher trophic levels.

Neural Cell Adhesion Molecule L1 Modulates Type I But Not Type II Inner Ear Spiral Ganglion Neurite Outgrowth in an In Vitro Alternate Choice Assay - Yves Brand; Michael Sung; Eduardo Chavez; Eric Wei; Kwang K. Pak; Gary D. Housley; Daniel Bodmer; Allen F. Ryan (Journal of Molecular Neuroscience, 2013)

The Tensile and Viscoelastic Properties of Aortic Valve Leaflets Treated with a Hyaluronidase Gradient - Hubert Tseng; Eric J. Kim; Patrick S. Connell; Salma Ayoub; Jay V. Shah; K. Jane Grande-Allen (Cardiovascular Engineering and Technology, 2013)

A review of the abuse potential assessment of atomoxetine: a nonstimulant medication for attention-deficit/hyperactivity disorder - Himanshu P. Upadhyaya; Durisala Desaiah; Kory J. Schuh; Frank P. Bymaster; Mary J. Kallman; David O. Clarke; Todd M. Durell; Paula T. Trzepacz; David O. Calligaro; Eric S. Nisenbaum; Paul J. Emmerson; Leslie M. Schuh; et al. (Psychopharmacology, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Global Competency and Issues in Contemporary Education / Agroforestry - Susan Moore; Erin Sills; Lee Allen; Douglas Frederick; Frederick Cubbage; John Garland; Julie Lydick; Gordon Holley; Jodi Roberts; Stephen Grado; Zhu Ning; Shannon Fowler; et al. (Journal of Forestry, 2011)
34We performed a five year integrated research, extension and education project aimed at strengthening global competence of students and faculty through collaboration in forestry. We sought to improve our students' ability to cooperate, increase their understanding of global dynamics of forestry markets and enhance their knowledge of various approaches to forest management and conservation with Chile as the focus. The project had four key components: (1) facilitate faculty and student involvement in Chile through Spanish language training, a website, and visits by Chilean faculty; (2) support NC State faculty and student research and study in Chile through travel grants and study tours; (3) build on faculty sabbaticals in Chile by funding student research assistants; and (4) disseminate information from Chile through multiple channels to both the university and professional communities. The faculty exchange visits; graduate student research; and participation of NCSU students, faculty and staff in the study tours to Chile had substantial effects when the participants returned to the US and disseminated information about their experiences through both formal and informal mechanisms. Both students and faculty at NCSU are more aware of forestry research, policy and management in Chile. Faculty at NCSU and Chilean universities Universidad de Concepción and Universidad de Austral have established a strong basis for collaboration and are continuing to work together on funding proposals, research, and papers. Students who participated in the study tours learned about both the culture and forestry in Chile, including similarities, differences, and lessons for the US. This presentation will describe the activities, outcomes and ongoing impacts of the project.

Menopausal hormone therapy and risk of ovarian cancer in the European prospective investigation into cancer and nutrition - Konstantinos K. Tsilidis; Naomi E. Allen; Timothy J. Key; Laure Dossus; Rudolf Kaaks; Kjersti Bakken; Eiliv Lund; Agnès Fournier; Christina C. Dahm; Kim Overvad; Louise Hansen; Anne Tjønneland; et al. (Cancer Causes & Control, 2011)

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

Variation in Physiological Stress between Bridge‐ and Cave‐Roosting Brazilian Free‐Tailed Bats - LOUISE C. ALLEN; AMY S. TURMELLE; ERIC P. WIDMAIER; NICKOLAY I. HRISTOV; GARY F. MCCRACKEN; THOMAS H. KUNZ (Conservation Biology, 2011)
Since the late 1980s, Brazilian free‐tailed bats ( Tadarida brasiliensis ) have increasingly used bridges as roosts in the southern United States. We examined differences in blood cortisol levels, body condition, and parasite load, as measures of physiological stress in bats roosting in bridges and bats roosting in caves. We collected data during three periods, coinciding with female phases of reproduction. For all measures, bats were captured during the nightly emergence from the roost and immediately sampled. Cortisol levels were significantly higher during pregnancy and lactation and in individuals with lower body‐condition scores (length of forearm to mass ratio) and significantly higher in bats roosting in caves than in those roosting in bridges. Thus, we concluded that individuals of this species that roost in bridges are not chronically stressed and seem to be unaffected by human activities present at bridges. This is a rare documented instance where a human‐dominated environment does not appear to be adversely affecting the physiological health of a free‐ranging animal .

Diversity and distribution of microbial long‐chain fatty acid biosynthetic genes in the marine environment - Christine N. Shulse; Eric E. Allen (Environmental Microbiology, 2011)
Summary Bacterial production of long‐chain fatty acids via a polyketide synthase‐related mechanism has thus far only been investigated in isolate‐based studies. Here, the genetic capacity for production of long‐chain fatty acids was investigated using a culture‐independent approach. PCR primers targeting the keto‐acyl synthase (KS) domain of the pfaA gene involved in omega‐3 polyunsaturated fatty acid (PUFA) biosynthesis were used to construct clone libraries to investigate KS sequence diversity in disparate marine habitats. Of the 446 sequences recovered, 123 (27.6%) clustered with KS sequences involved in the synthesis of eicosapentaenoic acid (EPA, C20:5 n ‐3), docosahexaenoic acid (DHA, C22:6 n ‐3) and arachidonic acid (AA, C20:4 n ‐6). The remaining 72.4% of clones formed environmental‐only groups or grouped with the KS domains of pfaA homologues from organisms producing unidentified products. In total, 17 groups were recovered – four known and 13 newly identified. A query of metagenomic data sets revealed sequences related to EPA KS domains, as well as sequences related to four environmental‐only groups discovered in the clone libraries. The phylogenetic affiliation and end product of these environmental‐only KS clusters is unknown. These findings reveal a widespread capacity for long‐chain fatty acid production in marine microorganisms, including biosynthetic pathways not yet characterized.

Parasites of European hedgehogs (Erinaceus europaeus) in Britain: epidemiological study and coprological test evaluation - Gabriella Gaglio; Simon Allen; Lee Bowden; Mark Bryant; Eric R. Morgan (European Journal of Wildlife Research, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

A note on reviving the Goddard Satellite-based Surface Turbulent Fluxes (GSSTF) dataset - Chung-Lin Shie; Long S. Chiu; Robert Adler; Eric Nelkin; I. -I. Lin; Pingping Xie; Feng-Chin Wang; R. Chokngamwong; William Olson; D. Allen Chu (Advances in Atmospheric Sciences, 2009)

Ethanol intake and the risk of pancreatic cancer in the European prospective investigation into cancer and nutrition (EPIC) - Sabine Rohrmann; Jakob Linseisen; Alina Vrieling; Paolo Boffetta; Rachael Z. Stolzenberg-Solomon; Albert B. Lowenfels; Majken K. Jensen; Kim Overvad; Anja Olsen; Anne Tjonneland; Marie-Christine Boutron-Ruault; Francoise Clavel-Chapelon; et al. (Cancer Causes & Control, 2009)

The development and evaluation of a soil moisture index - Eric D. Hunt; Kenneth G. Hubbard; Donald A. Wilhite; Timothy J. Arkebauer; Allen L. Dutcher (International Journal of Climatology, 2009)
Soil water is an important parameter in the hydrological balance and is essential for understanding land–surface interactions. While spatial coverage of soil water observations is poor across most of the United States, impedance probes have been used to measure soil water throughout Nebraska in the Automated Weather Data Network (AWDN) since 1999. With 8 years of continuous data at selected sites, we were able to derive a Soil Moisture Index (SMI) that is based on an actual water content (θ) and a known field capacity and wilting point. The SMI is a continuous function and is scaled from 5.0 to − 5.0, with 5.0 representing θ at field capacity and − 5.0 representing θ at wilting point. Since the inception of the soil water network in 1999, periodic episodes of drought have affected all areas of Nebraska. Thus, the SMI was used in this study to analyse growing seasons (1 April to 1 October) from 1999 to 2006 at six selected sites throughout Nebraska. The SMI proved to be effective at depicting the onset of drought and at identifying soil recharge, or lack thereof, when heavy rainfall events followed a significant dry spell. Copyright © 2008 Royal Meteorological Society

Group formation and anemone use in captively reared anemonefish (Amphiprion frenatus) - Eric K. Bollinger; Paul V. Switzer; Jesse Pfammatter; Jason Allen (Ichthyological Research, 2008)

Metabolic versatility of the Riftia pachyptila endosymbiont revealed through metagenomics - Julie C. Robidart; Shellie R. Bench; Robert A. Feldman; Alexey Novoradovsky; Sheila B. Podell; Terry Gaasterland; Eric E. Allen; Horst Felbeck (Environmental Microbiology, 2008)
Summary The facultative symbiont of Riftia pachyptila , named here Candidatus Endoriftia persephone , has evaded culture to date, but much has been learned regarding this symbiosis over the past three decades since its discovery. The symbiont population metagenome was sequenced in order to gain insight into its physiology. The population genome indicates that the symbionts use a partial Calvin–Benson Cycle for carbon fixation and the reverse TCA cycle (an alternative pathway for carbon fixation) that contains an unusual ATP citrate lyase. The presence of all genes necessary for heterotrophic metabolism, a phosphotransferase system, and dicarboxylate and ABC transporters indicate that the symbiont can live mixotrophically. The metagenome has a large suite of signal transduction, defence (both biological and environmental) and chemotaxis mechanisms. The physiology of Candidatus Endoriftia persephone is explored with respect to functionality while associated with a eukaryotic host, versus free‐living in the hydrothermal environment.

The Development of Pine Plantation Silviculture in the Southern United States - Thomas R. Fox; Eric J. Jokela; H. Lee Allen (Journal of Forestry, 2007)
In the 1950s there were vast acreages of cutover forestland and degraded agricultural land across the South. Less than 2 million ac of southern pine plantations existed at that time. By the end of the 20th century, there were 32 million ac of southern pine plantations in the US South and this region is the wood basket of the world. The success story that is southern pine forestry was facilitated by the application of research results generated through cooperative work of the US Forest Service, southern forestry schools, state forestry agencies, and forest industry. This article reviews the contributions of applied silvicultural research in tree improvement, nursery management, site preparation, weed control, and fertilization to plantation forestry in the South. These practices significantly increased productivity of southern pine plantations. Plantations established in the 1950s and 1960s, which produced less than 90 ft3 ac−1 yr−1, have been replaced by plantations established in the 2000s, which may produce in excess of 400 ft3 ac−1 yr−1. Currently, southern pine plantations are among the most intensively managed forests in the world. Growth of plantations managed using modern, integrated, site-specific silvicultural regimes now can rival that of plantations of fast-growing exotic species in the Southern Hemisphere.

Sex differences in the contribution of nicotine and nonpharmacological stimuli to nicotine self-administration in rats - Nadia Chaudhri; Anthony R. Caggiula; Eric C. Donny; Sheri Booth; Maysa A. Gharib; Laure A. Craven; Shannon S. Allen; Alan F. Sved; Kenneth A. Perkins (Psychopharmacology, 2005)

Predicting Oral Absorption of Drugs: A Case Study with a Novel Class of Antimicrobial Agents - Allen R. Hilgers; Donald P. Smith; John J. Biermacher; Jeffrey S. Day; Jana L. Jensen; Sandra M. Sims; Wade J. Adams; Janice M. Friis; Joe Palandra; John D. Hosley; Eric M. Shobe; Philip S. Burton (Pharmaceutical Research, 2003)

Ecosystem response to bivalve density reduction: management implications - Richard Dame; David Bushek; Dennis Allen; Alan Lewitus; Don Edwards; Eric Koepfler; Leah Gregory (Aquatic Ecology, 2002)

MHC class I restricted T cell responses tolisteria monocytogenes, an intracellular bacterial pathogen - Alyce Finelli; Kristen M. Kerksiek; S. Elise Allen; Natalia Marshall; Roberto Mercado; Ingrid Pilip; Dirk H. Busch; Eric G. Pamer (Immunologic Research, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)